Przeobrażenia nurtu kulturowego w zarządzaniu - Pierzchawka, Sylwia (Transformation of organizational culture trend's in management, 2005)
The purpose of this paper is to show cultural attributes evolution from classic management foundations to contemporaneous management conceptions. Moreover, in this paper is a try to specify an important changes as a result from transformation of management by organizational culture.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1092, s. 658-665